2017
DOI: 10.1038/s41598-017-13304-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic induction of hypometabolism by ablation of MC4R does not suppress ALS-like phenotypes in the G93A mutant SOD1 mouse model

Abstract: Dysfunction and death of motor neurons leads to progressive paralysis in amyotrophic lateral sclerosis (ALS). Recent studies have reported organism-level metabolic dysfunction as a prominent but poorly understood feature of the disease. ALS patients are hypermetabolic with increased resting energy expenditure, but if and how hypermetabolism contributes to disease pathology is unknown. We asked if decreasing metabolism in the mutant superoxide dismutase 1 (SOD1) mouse model of ALS (G93A SOD1) would alter motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…increased metabolic rate) seen in SOD1 G93A mice (Scaricamazza et al, 2020 ; Steyn et al, 2020 ). This is of clinical importance as hypermetabolism is associated with poor outcomes in mouse models of ALS and in human ALS (Doshi et al, 2017 ; Dupuis et al, 2004 ; Fayemendy et al, 2021 ; Jésus et al, 2018 ; Scaricamazza et al, 2020 ; Steyn et al, 2018 ). In 2020, we demonstrated that treatment of SOD1 G93A mice with the metabolic modulator ranolazine was able to improve locomotor function, decrease metabolic rate and partially rescue the dysfunction of muscle metabolism in SOD1 G93A mice (Scaricamazza et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…increased metabolic rate) seen in SOD1 G93A mice (Scaricamazza et al, 2020 ; Steyn et al, 2020 ). This is of clinical importance as hypermetabolism is associated with poor outcomes in mouse models of ALS and in human ALS (Doshi et al, 2017 ; Dupuis et al, 2004 ; Fayemendy et al, 2021 ; Jésus et al, 2018 ; Scaricamazza et al, 2020 ; Steyn et al, 2018 ). In 2020, we demonstrated that treatment of SOD1 G93A mice with the metabolic modulator ranolazine was able to improve locomotor function, decrease metabolic rate and partially rescue the dysfunction of muscle metabolism in SOD1 G93A mice (Scaricamazza et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the melanocortin pathway, a critical regulator of energy homeostasis and food intake in the hypothalamus [ 184 ], was hypothesized to contribute to imbalanced energy homeostasis in ALS patients [ 67 ] and mice [ 201 ]. However, reducing energy expenditure and inducing hyperphagia by targeting this pathway in mutant SOD1 G93A mice did not improve motor function or lifespan [ 53 ]. While the cause and importance of dysregulated energy homeostasis in human ALS remains to be established, body weight loss is an important prognostic factor in patients [ 149 ].…”
Section: Systemic Metabolism Correlates To Als Disease Coursementioning
confidence: 99%